Bayang-Bayang Filsafat Yunani dalam Siluet Ushul Fikih - Ubaidillah, Ahmad (Universitas Islam Lamongan, 2023)
Abstract: This paper aims to elaborate on the intersection of ushul fiqh with the logic of Greek philosophy. This study also tries to explore whether there is contact between ushul fiqh scholars and Greek philosophical theories in formulating ushul fiqh science. This research is a library research by collecting data using books, articles, and the like. The data analysis used is content analysis method. The results of the research show that the entry of Greek philosophy into the Islamic world led to reconciliation. They bring together two different views. Their efforts eventually became a tool in the spread of philosophy and its penetration into Islamic studies, including ushul fiqh. Al-Shafi'i, as the first scholar to systematically formulate the science of ushul fiqh, should be suspected of being influenced by Greek philosophy, especially the logic of Aristotle's syllogism. The examples and similes in qiyas as well as the logic of Aristotle's syllogism show this influence. Qiyas, which originally meant dynamic free thought, changed in the post-Shafi'i era to become thought governed by important premises originating from the holy texts of the Qur'an and al-Hadith. As a result, qiyas becomes less productive because there are no truly new legal discoveries. The change was allegedly due to the inclusion of Aristotle's syllogistic logic.Keywords: Uhsul Fiqh, al-Syafi’i’s Qiyas’, Greek Philosophy, Aristotle's Syllogistic Logic